Pengaruh Gaya Hidup Berbelanja, Nilai Hedonis, Endorse Sosial Media Instagram Terhadap Minat Beli Pada Distro Lucky Light Candy Mataram - I Nyoman Ari Sutrisna; Baiq Ertin Helmida; Nendy Pratama Agusfianto (Kredibel: Jurnal Ilmiah Manajemen, 2025)
This research aims to determine the influence of shopping lifestyle, hedonic values, and Instagram social media endorsements on purchasing interest in the Lucky Light Candy Mataram distro. The type of research is associative and the sampling technique used is non-probability sampling. The sample used was 50 respondents from customers at the Lucky Light Candy Distro. The analytical method used is multiple linear regression analysis. The results of the multiple linear regression analysis are Y = 0,756 + 0,018X1 + 0,375X2 + 0,507X3. The results of this research also show that the t test (partial) states that the shopping lifestyle variable is not significant with the t value, namely 0,092 < ttabel and significant value 0,927 > 0,05, the hedonic value variable has a significant effect with a t-count value of 4.044 > ttable and a significant value of 0.000 < 0.05, the Instagram social media endorsement variable has a significant effect with a t-count value of 4.366 > ttable and a significant value of 0.000 < 0.05. Based on the F test (simultaneous), it is stated that the variables Shopping Lifestyle, Hedonic Value, and Instagram Social Media Endorsement influence simultaneously or simultaneously on buying interest with a calculated F value of 97.179 > F table and a significant value of 0.000 < 0.05.